Framing Komunikasi Kesehatan dalam Pendidikan Agama Islam di Media Baru - K. Y. S. Putri; Zulhamri Bin Abdullah; Dini Safitri; Lipur Sugiyanta; Angelita Kania Ramdan (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2020)
Health communication is needed by the Indonesian people. Islamic education greatly facilitates all forms of health for humanity. This study uses a new media object that is the national media Twitter which contains health information in 2019. The research problem formulation is how to frame health communication in Islamic religious education in new media? The purpose of this study was to determine the health communication framing in Islamic religious education in new media. Health communication is the art of informing influencing and motivating individuals, institutions and society about important matters in the health sector in improving the quality of life and health of individuals in society. The results of the study, the dimensions of informing, influencing, motivating individuals, and society through multilevel Twitter results. In the personal health information unit, this information is very often shared by the cyber media. However, if it is associated with the healthy behavior of new media users, it is seen to have followed. In public health information units such as sneezing and littering: this information is often shared by new media. Cybermedia users are very following.